Comparison of DNA Isolation Results with Simple Methods and Kits in Samples of Psidium guajava Leaves - Yuanita Rachmawati; Romyun Alvy Khoiriyah (Biotropic : The Journal of Tropical Biology, 2018)
DNA isolation is one of a series of methods that must be carried out on the basic techniques of Molecular Biology Analysis. Especially PCR-based molecular marking techniques. Many ways are done in DNA isolation. This study discusses the comparison of the results of DNA isolation using two methods. Simple DNA isolation methods and using Kit. Samples of Psidium guajava leaves used were taken from 15 different locations used. In general, DNA isolation methods include three steps, namely destruction, precipitation, and purification. Simple DNA isolation is done with detergents, alcohol groups, which are commonly available in the laboratory. Methods of DNA isolation with KIT are carried out according to the Promega Universal Wizard KIT protocol. The comparison results are seen from spectrophotometric absorption Å230 nm, Å260 nm, Å280 nm, Å320 nm, ratio Å260/Å230, ratio Å260/Å280 to see DNA purity, protein concentration before purification step, and DNA concentration produced. The results showed that there were no statistically significant differences in the results of DNA isolate spectrophotometry. However, the use of KIT with modified protocols is more recommended if researchers want to carry out DNA analysis more precisely and accurately. Keywords: DNA isolation, spectrophotometry, DNA concentration and purity